Konsep Business Judgement Rule dalam Perspektif Maṣlaḥah Mursalah: The Concept of Business Judgement Rule in the Perspective of Maṣlaḥah Mursalah - Anisatur Rohmah; Ahmad Musadad (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
This research aims to analyze the benefits of implementing the Business Judgment Rule concept when viewed from the perspective of maṣlaḥah murlah. The method used in this research is a qualitative research method with a normative juridical approach which makes the law the center of its study with the aim of providing legal arguments as a basis for whether the application of the Business Judgment Rule doctrine can be detrimental or not if viewed from the perspective of maṣlaḥah murlah which is then processed. into descriptive analysis. The results of this research show that the concept of the Business Judgment Rule doctrine is a concept that provides information to company directors regarding business decisions by considering various factors, namely the existence of good faith, prudence and accountability. Apart from that, the Business Judgment Rule doctrine has been widely used in several cases, especially in Indonesia. This means that the Business Judgment Rule doctrine, if seen from the maṣlaḥah murlah's point of view, does indeed bring benefits to the point of being a reference in a trial, even though in its implementation there is still a lack of socialization and education regarding the Business Judgment Rule doctrine within the scope of institutions or law enforcement officials.